Palmitoylation as a Key Regulator of Ras Localization and Function - Busquets-Hernández, Carla; Triola, Gemma (Frontiers in Molecular Biosciences, 2021)
Ras proteins require membrane association for proper function. This process is tightly regulated by reversible palmitoylation that controls not only the distribution over different subcellular compartments but also Ras compartmentalization within membrane subdomains. As a result, there is a growing interest in protein palmitoylation and the enzymes that control this process. In this minireview, we discuss how palmitoylation affects the localization and function of Ras proteins. A better understanding of the regulatory mechanism controlling protein lipidation is expected to provide new insights into the functional role of these modifications and may ultimately lead to the development of novel therapeutic approaches.